Objective and automated assessment of surgical technical skills with IoT systems: A systematic literature review - Castillo-Segura, Pablo; Fernández-Panadero, Carmen; Alario-Hoyos, Carlos; Muñoz-Merino, Pedro J.; Delgado Kloos, Carlos (Artificial intelligence in medicine, 2021)
•Systematic literature review on objective and automated assessment of surgical technical skills.•537 papers published after 2013 screened and 101 analyzed in detail.•Main sensors: mechanical/electromagnetic for tool tracking and IMU for body tracking.•Indicators (e.g., path length, smoothness) to distinguish between levels of expertise.•SVM and Neural Networks are the main methods/algorithms for processing the data. The assessment of surgical technical skills to be acquired by novice surgeons has been traditionally done by an expert surgeon and is therefore of a subjective nature. Nevertheless, the recent advances on IoT (Internet of Things), the possibility of incorporating sensors into objects and environments in order to collect large amounts of data, and the progress on machine learning are facilitating a more objective and automated assessment of surgical technical skills. This paper presents a systematic literature review of papers published after 2013 discussing the objective and automated assessment of surgical technical skills. 101 out of an initial list of 537 papers were analyzed to identify: 1) the sensors used; 2) the data collected by these sensors and the relationship between these data, surgical technical skills and surgeons’ levels of expertise; 3) the statistical methods and algorithms used to process these data; and 4) the feedback provided based on the outputs of these statistical methods and algorithms. Particularly, 1) mechanical and electromagnetic sensors are widely used for tool tracking, while inertial measurement units are widely used for body tracking; 2) path length, number of sub-movements, smoothness, fixation, saccade and total time are the main indicators obtained from raw data and serve to assess surgical technical skills such as economy, efficiency, hand tremor, or mind control, and distinguish between two or three levels of expertise (novice/intermediate/advanced surgeons); 3) SVM (Support Vector Machines) and Neural Networks are the preferred statistical methods and algorithms for processing the data collected, while new opportunities are opened up to combine various algorithms and use deep learning; and 4) feedback is provided by matching performance indicators and a lexicon of words and visualizations, although there is considerable room for research in the context of feedback and visualizations, taking, for example, ideas from learning analytics.